Pengaruh Pertumbuhan Perusahaan, Ukuran Perusahaan, Struktur Modal, dan Return on Equity Terhadap Kebijakan Dividen - Rosalita, Dino; Suyatmin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the impact of company growth, company size, capital structure, and return on equity on dividend policy. The population used in this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022. The sampling technique employed is purposive sampling. The total sample size is 178 for the period 2020-2022. Outliers were removed from the sample, leaving 124 usable observations. The analysis was conducted using multiple linear regression with SPSS version 25. The results show that company growth has a significant impact on dividend policy, while company size, capital structure, and return on equity do not have a significant effect on dividend policy for manufacturing companies listed on the Indonesia Stock Exchange during the period 2020-2022.